HUBUNGAN ANTARA KEMAMPUAN PENGELOLAAN EMOSI DENGAN PERILAKU AGRESIF PESERTA DIDIK - Triratnasari, Ida - (Bimbingan dan Konseling, 2014)
The ability of emotional control has important role in individual development process.Here, individual means the students. The reaction and expression of students emotional labile anduncontrolled that have impact in individual and social life woos still. Dealing with that fact, so theresearched want to study about the correlation between the ability of students in controllingemotion and aggressive behavior. The purposes of this relearned are: 1) To described of studentscontrolling in handling emotion. 2) To describe about students aggressive behavior. 3) Controllingto describe, about correlation both students aggressive behavior at SMP Negeri 23 Padang.Conduct this research in to actually, in this research the researcher tries to descriptive qualitativeby analysis statistic correlation. Population of this research is students at VII and VIII at SMPNegeri 23 Padang, and the amount of samples are around 83 students that is chosen from 484students at SMP Negeri 23 Padang. In this researcher the research proportional using a randomsampling, meanwhile to collect the data, the researcher instrument questionnaire in this research,the researcher analyze the data by using percentage analysis, meanwhile for testing hypothesis tofind out the result, the researcher use formula Pearson product moment correlation, in analysis thedata, the researcher use program Microsoft excel and SPSS program version 16.00. findings of thisresearch are: 1) The ability of students control emotion is categorized in good category. 2)Aggressive behavior is categorized as low category. 3) The correlation of students ability incontrol emotion and rhitung 0,366 > rtabel 0,213 in df 81 and the significant 0,01 (sig < 0,05).Based on the finding above that there are correlational both students ability in handling emotionand students aggresive behavior at SMP Negeri 23 Padang.